Penerapan Model Pembelajaran Group Investigation untuk Meningkatkan Partisipasi Siswa SMA dalam Pembelajaran Biologi: (The Implementation of the Group Investigation Learning Model to Increase Student Participation In Biology Learning) - Rafyka Basri; Pitri Hairani Dongoran; Dinda Syafitri; Agista Putri Wahyudi Silaban; Indayanna Febriani Tanjung (BIODIK, 2022)
This study aims to determine how the implementation of the Group Investigation learning strategy in increasing the participation of high school students in learning biology. This research is a type of classroom action research with the model developed by Kemmis and Mc. Taggart. The subjects in this study were students of class XI MIA-2 MAS Raudhatul Akmal Batang Kuis Foundation, with a total of 21 students. The data collection technique in this study used observation in the form of observation. This research consisted of two cycles and each cycle consisted of two meetings. The data analysis technique in this research is descriptive quantitative. The success criteria determined for student participation in learning are 75%. From the results of research conducted by researchers, the study of the investigative group model was effectively used during learning in class XI IPA -2 Yayasan Pendidikan Raudhatul Akmal Batang Kuis with several improvements, as evidenced by the results of research in each cycle. The results of increasing student participation in Biology learning by applying the group investigation learning model for the first cycle was 44% and the second cycle was 81.29%. Key words: Group Investigation, student Participation, Biology Learning. Â  ABSTRAK Penelitian ini didasari dari pentingnya partiipasi siswa dalam pembelajaran. Tujuan dalam penelitian ini dimaksudkan untuk melihat bagaimana model penerapan model pemeblajaran group investigation dalam meningkatkan partisipasi siswa dalam pembelajaran biologi. Penelitian ini menggunakan Penelitian tindakan kelas (PTK) dimana siswa kelas XI IPA-2 MAS Yayasan Pendidikan Raudhatul Akmal Batang kuis sebagai subjek dalam penelitian ini. Data dikumpulkan memlalui lembar observasi dengan kriteria keberhasilan mencapai 75 %. Dari hasil penelitian diliat terjadinya peninkatan partisipasi siswa di dari 44 % pada siklus I dan 81.29% pada siklus II. Kata kunci: Group Investigation, Partisipasi Siswa, Pembelajaran Biologi